Perencanaan Rekonfigurasi Penyulang Mojoanyar Dengan Pengalihan Beban Ke Penyulang Elkishi Di Daerah Kawasan Industri Mojosari Pada PT PLN (Persero) UP3 Mojokerto - Mochammad Mieftah; Heri Sungkowo; Mudjiono (Elposys: Jurnal Sistem Kelistrikan, 2022)
Mojosari is a customer area consisting of industrial customers and high power customers. Currently, the demand for electrical energy in the area is supported by the Mojoanyar Feeder, which is supplied by the Transformer I Pulling Substation I with a capacity of 30 MVA. The reconfiguration of the feeder was carried out for several reasons, one of which was the addition of power from an industrial customer in the Mojoanyar Feeder area of PT PLN (Persero) ULP Mojosari, namely PT Sinar Karya Duta Abadi (Arwana). If there is additional power, the additional load capacity also increases in a feeder. If the load capacity increases, the current flowing in the conductor also increases. It can be seen from the loading data in February 2021 that the maximum current flowing in the Mojoanyar Feeder during the day is 210 A, the maximum current flowing in the Mojoanyar Feeder at night is 215 A. And if there is a disturbance near the area, the Mojoanyar Feeder will not maneuver because the load is close to the maximum. Therefore, PT PLN (Persero) ULP Mojosari plans a reconfiguration of the feeder by transferring the burden of the Mojoanyar feeder.The analysis was carried out using the simulation program ETAP Power Station 12.6.0. and manual calculations according to standards. After being reconfigured, the Mojoanyar Feeder experienced a decrease in the value of the voltage drop from 8.78% to 7.86%. Mojoanyar feeders experienced a decrease in losses of 5.84% compared to before the reconfiguration of 10.4%